Assessment of the Food Habits and School Feeding Programme of Pupils in a Rural Community in Odogbolu Local Government Area of Ogun State, Nigeria - Olusanya, J.O. (Pakistan Journal of Nutrition, 2010)
The food habits and school feeding programme of pupils in a rural community in Odogbolu local government area of Ogun State, Nigeria was assessed in this study. A total of 68 pupils from primaries I to III in both public and private primary schools were involved in the study. It was found that majority of the school children had three meals daily. Majority of the pupils do not bring food to school from home. The amount of money brought to school to purchase mid-day meal foods was higher with pupils from private school than those from public schools. However, generally the quantity and quality of the mid-day meal purchased on both schools were poor and therefore did not have significant contribution of their nutritional status.